2012
DOI: 10.1055/s-0031-1298627
|View full text |Cite
|
Sign up to set email alerts
|

A Prenylated Flavanone from Dalea elegans Inhibits Rhodamine 6 G Efflux and Reverses Fluconazole-Resistance in Candida albicans

Abstract: In previous studies, 2',4'-dihydroxy-5'-(1''',1'''-dimethylallyl)-6-prenylpinocembrin, a prenylated flavonoid isolated from Dalea elegans roots, showed activity against multiresistant Staphylococcus aureus and Candida albicans, as well as an uncoupling effect on mitochondria and antioxidant activity. The aim of this study was to evaluate the inhibitory effects of 2',4'-dihydroxy-5'-(1''',1'''-dimethylallyl)-6-prenylpinocembrin and fluconazole on the efflux of rhodamine 6 G in azole-resistant C. albicans 12-99 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 18 publications
(27 reference statements)
0
15
0
19
Order By: Relevance
“…The upregulations of multidrug efflux pump controlled by Cdr1p, Cdr2p belonging to ATP-binding cassette superfamily (APC transporter) and Mdr1p, a member of major facilitator superfamily (MFS) were implicated in most fluconazole-resistant C. albicans strains (Niimi et al 2004;Holmes et al 2012;Prasad and Rawal 2014) as FLC was a substrate for CDR1, CDR2, and MDR1 (Kohli et al 2001;Nakamura et al 2001). Rhodamine 6G was the most common used fluorescent dye of ABC pump substrate requiring ATP as energy to observe transporter-mediated FLC resistance (Lamping et al 2007;Peralta et al 2012). Our experiments showed that FLC alone failed to lead to rhodamine 6G accumulation in the intracellular space in C. albicans z2003 due to active efflux pump (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The upregulations of multidrug efflux pump controlled by Cdr1p, Cdr2p belonging to ATP-binding cassette superfamily (APC transporter) and Mdr1p, a member of major facilitator superfamily (MFS) were implicated in most fluconazole-resistant C. albicans strains (Niimi et al 2004;Holmes et al 2012;Prasad and Rawal 2014) as FLC was a substrate for CDR1, CDR2, and MDR1 (Kohli et al 2001;Nakamura et al 2001). Rhodamine 6G was the most common used fluorescent dye of ABC pump substrate requiring ATP as energy to observe transporter-mediated FLC resistance (Lamping et al 2007;Peralta et al 2012). Our experiments showed that FLC alone failed to lead to rhodamine 6G accumulation in the intracellular space in C. albicans z2003 due to active efflux pump (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The pellets were washed three times by sterile PBS. As efflux of rhodamine-6G from Candida cells required the presence of glucose, glucose dissolved in PBS was coincubated with the pellets to the final concentration of 2 mmol/L at 37 C 200 rpm for 1 h. The suspension was centrifuged at 3000 g. An aliquot of supernatant (100 mL) was removed and detected at an excitation wavelength of 525 nm and an emission wavelength of 550 nm with an inverted fluorescence microscope IX71 (Olympus, Tokyo, Japan) (Peralta et al 2012). …”
Section: Efflux Test Of Rhodamine-6gmentioning
confidence: 99%
See 1 more Smart Citation
“…1). These prenylated derivatives of pinocembrin have proven to be highly active in different biological activity assays (Ortega et al, 1996;Pé rez et al, 2003;Elingold et al, 2008;Peralta et al, 2012). Another species of Dalea was studied in our group, D. boliviana, and showed the presence of new prenylated flavanones active as tyrosinase inhibitors (Peralta et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…In the decades since, studies have shown that pinocembrin can significantly inhibit the activity of Penicillium italicum [60], Candida albicans [6165], Staphylococcus aureus [66,67,61,68,69,65,11], E. coli [70,61], Bacillus subtilis, Trichophyton mentagrophytes, Streptococcus mutans [71,65,19], and Neisseria gonorrhoeae [72]. Recently, Soromou et al [66] reported that pinocembrin reduced α-haemolysin production and attenuated α-haemolysin-mediated cell injury at low concentrations and protected mice from S. aureus -induced pneumonia.…”
Section: Inflammatory and Infectious Diseasesmentioning
confidence: 99%